2010
DOI: 10.1111/j.1095-8312.2010.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal abilities and spatial patterns in fragmented landscapes

Abstract: Recent theoretical studies suggest that the distribution of species in space has important implications for the conservation of communities in fragmented landscapes. Facilitation and dispersal are the primary mechanisms responsible for the formation of spatial patterns. Furthermore, disruptions in the formation of patterns arise after degradation, which can serve as an early indicator of stress in plant communities. Spatial dispersal ability and pattern formation were evaluated in 53 linear transects of 500 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 91 publications
0
25
1
2
Order By: Relevance
“…Using multiple data sets gave us the ability to distinguish effects of different aspects of the environment on dispersal syndromes including habitat quality, habitat patchiness and vegetation type. Several studies of humanfragmented landscapes have shown that species with more directed (vertebrate) dispersal are less vulnerable to fragmentation (Damschen et al 2008;Montoya et al 2008;Alados et al 2010). Our results suggest that communities on discontinuous patches of low-fertility soils are not necessarily composed of good dispersers.…”
Section: Discussionmentioning
confidence: 56%
“…Using multiple data sets gave us the ability to distinguish effects of different aspects of the environment on dispersal syndromes including habitat quality, habitat patchiness and vegetation type. Several studies of humanfragmented landscapes have shown that species with more directed (vertebrate) dispersal are less vulnerable to fragmentation (Damschen et al 2008;Montoya et al 2008;Alados et al 2010). Our results suggest that communities on discontinuous patches of low-fertility soils are not necessarily composed of good dispersers.…”
Section: Discussionmentioning
confidence: 56%
“…This is especially relevant in arid areas where species that have a restricted spatial dispersal are abundant because the space suitable for germination is scarce and it is advantageous to germinate close to the mother plant (Van Rheede van Outshoorn and Van Rooyen, 1999). Consequently, species that have restricted spatial dispersal (reduction of dispersal mechanisms or have anchorage mechanisms), which are predominant in arid regions (Ellner and Shmida, 1981;Gutterman, 1993;Navarro et al, 2009), are very sensitive to habitat fragmentation (Alados et al, 2010). In semi-arid areas in southeastern Spain, the isolation of remnant fragments had a negative effect on plant species richness (Alados et al, 2009a) and led to an increase in the differences in species composition among fragments (spatial variability in species distributions was greater than that expected from a random spatial distribution).…”
Section: Vegetation Spatial Patterns At Multiple Scalesmentioning
confidence: 99%
“…These conclusions on seed dispersal by trees might not apply universally. In contrast to Montoya et al [37], Alados et al [38] found that vertebrate-dispersed shrubs were more susceptible to fragmentation than other shrubs. The authors postulated that the reason for this was positive feedback between the abundance of a fruiting species on a given patch and the ability of that patch to attract appropriate animal seed dispersers (i.e.…”
Section: Are Animal Seed Dispersers Important To Plant Conservation?mentioning
confidence: 78%